Implementation of Good Corporate Governance in the Business and Operational Processes of PT BPR BKK Karangmalang (Perseroda) Sragen - Khairunissa Nareswari; Nahda, Katiya (Universitas Muhammadiyah Sorong, 2024)
This study aims to determine how good corporate governance impacts business and operational activities at PT BPR BKK Karangmalang (Perseroda) Sragen, especially in overcoming irregularities and promoting GCG, alignment of operational activities with GCG principles, GCG contribution in preventing fraud, and GCG effectiveness in improving financial performance. The qualitative research method involves observations and interviews with structural officials related to the topic. The results of this study indicate that the implementation of GCG can bring the company in a better direction from various sides. Effective and efficient GCG implementation can benefit the company, stakeholders, and society positively.